Regulation of Magnesium Matrix Composites Materials on Bone Immune Microenvironment and Osteogenic Mechanism - Nie, Xiaojing; Zhang, Xueyan; Lei, Baozhen; Shi, Yonghua; Yang, Jingxin (Frontiers in Bioengineering and Biotechnology, 2022)
Despite magnesium based metal materials are widely used in bone defect repair, there are still various deficiencies, and their properties need to be optimized. Composites synthesized with magnesium based metal as matrix are the research hotspot, and the host immune response after biomaterial implantation is very important for bone binding. By studying the immunoregulation of bone biomaterials, it can regulate the immune response in the process of osteogenesis and create a good local immune microenvironment, which is conducive to biomaterials to reduce inflammatory response and promote good bone binding. This article introduces the osteogenic mechanism of magnesium based metal materials and its regulation on bone immune microenvironment in detail.